Situation Analysis of Environmental Health in Nepal - jha, HB (Nepal Health Research Council (NHRC), 2016)
Background: Environmental health incorporates environmental issues affecting public health. The subject though important to the planners, policy makers, government and related institutions, was not given due weightage until the introduction of Nepal Environment Policy and Action Plan (NEPAP) in 1993. Increased population, uncontrolled urbanization, vehicle emission, industrialization, land degradation and biodiversity loss are some of the important factors responsible for the degradation of air, water, land and noise quality. Environmental problem is common both in rural and urban areas. But it is conspicuous more in urban areas, mainly in Kathmandu valley. As a result, the human health is affected. The biodiversity is affected to such an extent that a number of species have become extinct and the lives of many others are endangered. This study intended to conduct situational analysis of environmental health sector so that it could contribute towards developing plans and programs to mitigate the problems. Methods: Both primary and secondary sources of materials have been used for collection of data. The primary data have been collected through interview with key resource persons and field visit. Data collected from primary and secondary sources were compiled, processed and analyzed. Results: The Ministry of Population and Environment and Ministry of Health have developed policies, guidelines and standards in related field but they are not adequate particularly in environmental health sector. In the environmental sector, the ambient air pollution level mostly in urban areas has been affected due to the presence of parameters including particulate matter, carbon monoxide, carbon dioxide, sulphur dioxide and lead. Indoor air pollution largely by biomass has proved hazardous to public health due to the concentration of PM10 and other such factors. Additionally water quality is affected mainly due to the contamination of river water, underground water and surface water through the discharge of effluent of polluting industries and untreated sewerage in water. High level of bacteriological contamination of water largely caused by faecal contamination is a serious problem in Kathmandu. In the Terai, arsenic contamination is a matter of concern in certain pockets. Land is getting polluted through the haphazard use and misuse of chemicals and pesticides, household hazardous wastes, municipal solid wastes and hospital wastes. Changing environment has caused several health problems. Conclusions: The environmental health hasn't received adequate attention despite its need for better public health. Focus should be given towards development of skilled manpower, laboratory and equipment, information and database management and researches in order to improve the institutional capability of the environmental health institutions in Nepal. Keywords: environmental health; Nepal; situational analysis.